2001
DOI: 10.4141/a00-086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fish silage and fish fat on performance and egg quality of laying hens

Abstract: Kjos, N. P., Herstad, O., Skrede, A. and Øverland, M. 2001. Effects of dietary fish silage and fish fat on performance and egg quality of laying hens. Can. J. Anim. Sci. 81: 245-251. A total of 45 laying hens were fed a control diet, or one of four diets containing 50 g kg -1 fish silage and different levels of fish fat (1.8, 8.8, 16.8 or 24.8 g kg -1 ), to determine the effect of fish silage and fish fat in the diet on performance and egg quality. Fish silage did not affect feed intake, egg production, fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
(27 reference statements)
3
8
0
1
Order By: Relevance
“…Biological fish silage is considered a valuable source of LAB, which act as probiotics in silagefed animals bringing health benefits (Yin et al 2005;García et al 2007). Fish silage has adequate levels of essential amino acids (Vidotti et al 2003;Ramírez-Ramírez 2009), which can be used as a high nutritional value protein source for the feeding of different animal species such as broilers (Espe et al 1992;Kjos et al 2000;SantanaDelgado et al 2008;Al-Marzooqi et al 2010), pigs (Kjos et al 1999), laying hens (Kjos et al 2001), lambs (Barroga et al 2001), fish (Fagbenro and Jauncey 1998;Vidotti et al 2002;Borghesi et al 2008) and laying quails (Zinudheen et al 2008). It has been reported that the use of diets with fish oil and fish silage may increase the content of polyunsaturated (PUFA) and long-chain omega-3 (C20:1, C22:1, C22:5 and C22:6) fatty acids in pig and broiler meat (Kjos et al 1999(Kjos et al , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Biological fish silage is considered a valuable source of LAB, which act as probiotics in silagefed animals bringing health benefits (Yin et al 2005;García et al 2007). Fish silage has adequate levels of essential amino acids (Vidotti et al 2003;Ramírez-Ramírez 2009), which can be used as a high nutritional value protein source for the feeding of different animal species such as broilers (Espe et al 1992;Kjos et al 2000;SantanaDelgado et al 2008;Al-Marzooqi et al 2010), pigs (Kjos et al 1999), laying hens (Kjos et al 2001), lambs (Barroga et al 2001), fish (Fagbenro and Jauncey 1998;Vidotti et al 2002;Borghesi et al 2008) and laying quails (Zinudheen et al 2008). It has been reported that the use of diets with fish oil and fish silage may increase the content of polyunsaturated (PUFA) and long-chain omega-3 (C20:1, C22:1, C22:5 and C22:6) fatty acids in pig and broiler meat (Kjos et al 1999(Kjos et al , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…FS contained the most essential amino acids (methionine, leucine and glycine) compared to fish meal. Kjos et al (2001) reported that acid and fermented FS contains slightly lower amino acids content compared with fish meal especially lysine, methionine, cysteine and tryptophan. Nutritional value of silage may be improved by limiting the extent to which proteins are hydrolysed to polypeptides and free amino acids (Stone & Hardy 1986).…”
Section: Nutritive Value Of Fsmentioning
confidence: 99%
“…The diet with 3% fish silage had the lowest FCR and it did not differ significantly among the treatments. In an earlier study by Kjos et al (2001), the inclusion of upto 5% fish silage did not affect the egg production, egg quality or feed intake in the laying hens. Espe et al (1992) have reported a non significant effect of 30% dietary inclusion of fish silage on the feed efficiency in broiler chicks.…”
Section: Results and Discussion Egg Production And Feed Conversion Ramentioning
confidence: 61%